MINUMAN JELLY CINCAU DAPAT MENURUNKAN KADAR MALONDIALDEHID PLASMA PADA PRIA DEWASA PEROKOK - Purnamasari, Indah; Amalia, Leily (Jurnal Gizi dan Pangan, 2016)
The general objective of this study was to analyze the effect of intervention of the grass jelly on level of MDA (malondialdehyde) in adult male smokers. The design of this study was a quasi experiment with pre-post test with control. The subjects were divided into four groups, consisted of 1) control (K); that was not given any food intervention; 2) P1 that was given food intervention for 14 days; 3) P2 that was given food intervention for 21 days; and 4) P3 that was given food intervention for 28 days. Subjects were requested to consume grass jelly drink everyday as much as 200 g/d. All subjects had high level of MDA at pre-intervention. The result of this study shows that MDA levels of subjects at post-intervention in the treatment groups decreased significantly (p<0.05). The highest decrease was occured on P3 (49.82%). Hence, the intervention of grass jelly drink as much as 1 portion (200 g) could reduce MDA level of plasma; and the longer the intervention, the higher the reduction.Keywords: antioxidant, grass jelly drink, MDA